+0  
 
0
72
6
avatar+80 

can I multiply (2x+5y)(3x^2-4xy+2y^2)?

gadzooks1753  Nov 16, 2017
Sort: 

6+0 Answers

 #1
avatar
-1

Expand the following:
(2 x + 5 y) (3 x^2 - 4 x y + 2 y^2)

(3 x^2 - 4 x y + 2 y^2) (2 x + 5 y) = 2 x (3 x^2 - 4 x y + 2 y^2) + 5 y (3 x^2 - 4 x y + 2 y^2):
2 x (3 x^2 - 4 x y + 2 y^2) + 5 y (3 x^2 - 4 x y + 2 y^2)

2 x (3 x^2 - 4 x y + 2 y^2) = 2 x×3 x^2 + 2 x (-4 x y) + 2 x×2 y^2:
2×3 x x^2 - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2 x×3 x^2 = 2 x^(1 + 2)×3:
2×3 x^(1 + 2) - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

1 + 2 = 3:
2×3 x^3 - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2×3 = 6:
6 x^3 - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2 x (-4) x y = 2 x^2 (-4) y:
6 x^3 + -4×2 x^2 y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2 (-4) = -8:
6 x^3 + -8 x^2 y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2×2 = 4:
6 x^3 - 8 x^2 y + 4 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

5 y (3 x^2 - 4 x y + 2 y^2) = 5 y×3 x^2 + 5 y (-4 x y) + 5 y×2 y^2:
6 x^3 - 8 x^2 y + 4 x y^2 + 5×3 y x^2 - 4×5 y x y + 5×2 y y^2

5×3 = 15:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 4×5 y x y + 5×2 y y^2

5 y (-4) x y = 5 y^2 (-4) x:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 + -4×5 y^2 x + 5×2 y y^2

5 (-4) = -20:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 + -20 y^2 x + 5×2 y y^2

5 y×2 y^2 = 5 y^(1 + 2)×2:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 5×2 y^(1 + 2)

1 + 2 = 3:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 5×2 y^3

5×2 = 10:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 10 y^3

Grouping like terms, 6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 10 y^3 = 10 y^3 + (4 x y^2 - 20 x y^2) + (15 x^2 y - 8 x^2 y) + 6 x^3:
10 y^3 + (4 x y^2 - 20 x y^2) + (15 x^2 y - 8 x^2 y) + 6 x^3

4 (x y^2) - 20 (x y^2) = -16 (x y^2):
10 y^3 + -16 x y^2 + (15 x^2 y - 8 x^2 y) + 6 x^3

15 (x^2 y) - 8 (x^2 y) = 7 (x^2 y):
10y^3 - 16xy^2 + 7x^2y + 6x^3

Guest Nov 16, 2017
 #2
avatar+80 
-1

so i can multiply this

gadzooks1753  Nov 16, 2017
 #3
avatar+648 
-1

Yes.

AdamTaurus  Nov 16, 2017
 #4
avatar+80 
-1

is the answer 6x^3+7x^2y-16xy^2+10y^3

gadzooks1753  Nov 16, 2017
 #5
avatar+80 
-1

nevermind on that answer

gadzooks1753  Nov 16, 2017
 #6
avatar+648 
0

(2x+5y)(3x^2-4xy+2y^2)

First, multiply the first term in the first parenthesis by every term in the polynomial.

\((2x)(3x^2)+(2x)(-4xy)+(2x)(2y^2)+(5y)(3x^2-4xy+2y^2)\)

Simplify.

\((2x)(3x^2)=6x^3, (2x)(-4xy)=-8x^2y, (2x)(2y^2)=4xy^2\)

\(6x^3-8x^2y+4xy^2+(5y)(3x^2-4xy+2y^2)\)

Now distribute the 5y.

\(6x^3-8x^2y+4xy^2+(5y)(3x^2)+(5y)(-4xy)+(5y)(2y^2)\)

Simplify.

\((5y)(3x^2)=15x^2y, (5y)(-4xy)=-20xy^2, (5y)(2y^2)=10y^3\)

\(6x^3-8x^2y+4xy^2+15x^2y-20xy^2+10y^3\)

Reorganize.

\(6x^3-8x^2y+15x^2y+4xy^2-20xy^2+10y^3\)

Combine like terms.

\(-8x^2y+15x^2y=7x^2y, 4xy^2-20xy^2=-16xy^2\)

\(6x^3+7x^2y-16xy^2+10y^3\)

This is the same as Guest's answer but LaTeX makes it easier to read.

AdamTaurus  Nov 16, 2017

25 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details